Performance Comparison of Fault Tolerant PM Machine for Static Load Holding Application - Raminosoa, Tsarafidy; Gerada, Christopher; Othman, Md Nazri (Electric Machines and Drives Conference, 2009. IEMDC '09. IEEE International, 2009)
This paper looks in detail at a fault tolerant machine for direct drive application. The machine considered is a high pole number, concentrated wound machine developed for a safety critical aerospace application. The machine is designed to have a high p.u. inductance to limit short circuit current and negligible mutual inductance to have decoupled phase windings. Single and double layer winding configurations are compared. The machine has a heavy magnetic loading as its most onerous requirement is to hold a static load. High resulting air gap harmonics however induce substantial eddy current losses in the magnets and the solid rotor core. Due to the high thermal resistance path to these losses, the magnets may reach limiting temperatures during dynamic operation. This paper is set to analyze and compare two winding configurations and employ analytical modeling methods to evaluate the induced eddy current loss in the rotor.